(untitled) (Olhares, 2015)
The article reviews the technical and aesthetic influence from the polish director Jerzy Grotowski, who passed away in 1999, discussing the different currents which claim the grotowskian model. Schechner describes projects those develop research from Grotowski’s proposals, and set relationships up between those “designated” as heirs of the master, and other followers, analyzing the constitution of grotowskian tradition.